Student Version of the Teacher–Student Relationship Inventory (S-TSRI): Development, Validation and Invariance - Ang, Rebecca P.; Ong, Soo Lin; Li, Xiang (Frontiers in Psychology, 2020)
There is limited knowledge concerning children’s relationships with their teachers, and specifically, we lack a suitable, culturally appropriate measurement instrument for assessing the teacher-student relationship from the student’s perspective in Asia. This study used attachment theory as a theoretical framework to understand teacher-student relationships. Using a dataset from the Ministry of Education (MOE) of Singapore, the authors developed and validated a student version of the Teacher-Student Relationship Inventory (S-TSRI), with good psychometric properties for Singaporean children. The three-factor S-TSRI model comprising the factors satisfaction, instrumental help, and conflict was first established by exploratory factor analysis (EFA) and confirmed by confirmatory factor analysis (CFA). Through subsequent multigroup CFAs, we found that the factorial invariance was supported across gender, grade levels, and students of different academic levels, represented by the pass and fail groups. The structural model was tested in the total, pass and fail groups. For the total and pass groups, the factors satisfaction and instrumental help showed significant positive relationships with a sense of school belonging, and negative or nonsignificant relationships with aggression. The conflict factor showed a weaker negative or nonsignificant relationship with a sense of school belonging, and a positive relationship with aggression. For the fail group, identical results were obtained with one exception, and this was discussed in the light of the fail group having a different needs profile. Findings from this study show that the 14-item S-TSRI measure has robust psychometric properties, and yields scores that are reliable and valid in this large sample of primary school students from Singapore.